Konsep Dasar Manajemen Mutu dalam Perspektif Pendidikan Islam: Integrasi Nilai Spiritual dan Profesionalisme - Moch Rizwan Aprilianto; Mutiara Rahmawati (Jurnal Ilmiah Literasi Indonesia, 2025)
This research focuses on the basic concept of quality management from an Islamic education perspective by examining the integration of spiritual values and professionalism in managerial practices at MA Nurul Jadid, Probolinggo. The background of this research is based on the need for Islamic educational institutions to implement a quality system that prioritizes not only technical and administrative aspects but also profound Islamic values such as ikhlas (sincerity), amanah (trustworthiness), and ihsan (goodness). This research used a qualitative descriptive approach with a case study method. Data were collected through in-depth interviews, participant observation, and documentation studies with eight key informants. The results indicate that quality planning, implementation, and evaluation at MA Nurul Jadid are based on spiritual principles internalized in the institutional culture. These findings demonstrate that spirituality not only aligns with modern professionalism but also strengthens the moral legitimacy and effectiveness of holistic collaborative management. The implications of this research emphasize the importance of designing an Islamic education quality system that eliminates Islamic values as both a managerial and spiritual framework. These findings open new opportunities for the development of values-based quality management theory and provide strategic direction for future Islamic education quality policy.